Relationship of apolipoprotein E polymorphism with lipid profiles in atherosclerotic coronary artery disease - Ibrahim Elmadbouh; Yasser Elghobashy; Eman Abd-Allah; Ahmad-Ashraf Reda; Adnan Fathe; Safaa Tayel; Tarek Abd-Elhakim (The Egyptian Heart Journal, 2013)
Aims: The aim was to determine the relationship between apolipoprotein E (ApoE) gene polymorphisms and lipid profile in patients with coronary artery diseases (CAD), and its role in the prediction of the severity of carotid and coronary atherosclerosis. Methods and results: One hundred patients were classified by coronary angiography: 80 patients with CAD and 20 controls (normal coronary angiography). Clinical data, carotid sonography, blood lipid profiles and ApoE genotyping (PCR-RFLP) were assessed. CAD patients had significantly increased plasma lipid profiles and carotid intimal-wall thickness (IMT) versus controls. In CAD patients; ApoE genotype frequencies were E3/E3 = 62.50%, E2/E3 = 18.75%, E3/E4 = 17.50%, E2/E4 = 1.25%, E4/E4 = 0 and E2/E2 = 0. But, E3/E4 genotype was significantly higher than controls (P < 0.05). Also, in CAD patients; ApoE allele frequencies were E3 = 80.6%, E2 = 10.0% and E4 = 9.4% but, ApoE4 alleles were associated with higher cholesterol (P = 0.034) and LDL-c (P = 0.003), while ApoE2 alleles were associated with higher triglycerides (P = 0.037) versus ApoE3 alleles. However, odds ratio of CAD patients had higher risk with E2/E3 genotypes (2.5-fold), E2 alleles (2.2-fold) and E4 alleles (2.1-fold). Moreover, CAD patients with ApoE4 alleles had significantly higher carotid IMT (1.23 ± 0.26 mm vs 0.97 ± 0.2 mm ApoE3, P = 0.006; however, non-significant vs 1.10 ± 0.40 mm ApoE2 and also, ApoE2 vs ApoE3 alleles, P = 0.633) and left anterior descending (LAD) coronary artery stenosis (vs ApoE3 alleles, P = 0.016). Conclusion: Ischemic patients with carotid and coronary atherosclerosis had significantly higher integration of dyslipidemia and ApoE alleles (ApoE2 with hypertriglyceridemia and ApoE4 with hypercholesterolemia and higher LDL-c). ApoE polymorphism may be an important diagnostic risk biomarker and may implicate therapeutic intervention in atherosclerotic ischemic patients.